FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN DAGING AYAM BURAS DI PASAR TRADISIONAL KOTA MANADO - Mamuaja, Chaterine L; Rorimpandey, B; Wantasen, E; Dalie, S (Universitas Sam Ratulangi, 2020)
FACTORS AFFECTING DEMAND FOR NATIVE CHICKEN MEAT IN TRADITIONAL MARKET MANADO CITY. The objective of this study was to know the influence of native chicken meat price, taste and consumers’ income on the demand of native chicken meat in traditional market of Manado city. Accidental sampling method was use in this study. Fifty sample of consumers was randomly chosen in Bersehati market and 50 respondents taken in Pinasungkulan market. Therefore the total respondents included in this research was 100 consumers. The study showed that both overall and partially test indicated that chicken meat pice, consumers’ income and consumers’ appetite was significantly affecting demand for native chicken by consumers on traditional market in Manado city